Update and Outlook for 2003 of Florida's BMP Program for Vegetable Crops - Eric H. Simonne; Chad M. Hutchinson; Michael D. Dukes; George J. Hochmuth; Robert C. Hochmuth (EDIS)
This document is HS916, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: February 2003.